2021
DOI: 10.1016/j.sjbs.2020.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thiamazole on kainic acid-induced seizures in mice

Abstract: Kainic acid (KA) induced epileptic seizures in mice is a commonly used experimental model of epilepsy. Previous studies have suggested the roles of various neurotransmitters and oxidative stress in KA-induced seizures. An important role of hypothyroidism has also been suggested in epilepsy. Thiamazole (TZ) is an anti-hyperthyroid drug with antioxidant property. This study reports the effect of TZ on KA-induced epileptic seizures in mice, produced by intraperitoneal (IP) injection of KA (18 mg/kg). Prior to KA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In our work, tissue levels of MDA, a particular marker of lipid peroxidation, increased when kainic acid was produced (10 mg/kg), clearly suggesting increased oxidative stress in the hippocampus. MDA levels were also shown to be higher in a KA-induced epilepsy mouse ( Feng et al, 2021 ). A considerable rise in MDA has been associated with oxidative degradation in cellular proteins ( Miao et al, 2021 ), which we also found.…”
Section: Discussionmentioning
confidence: 98%
“…In our work, tissue levels of MDA, a particular marker of lipid peroxidation, increased when kainic acid was produced (10 mg/kg), clearly suggesting increased oxidative stress in the hippocampus. MDA levels were also shown to be higher in a KA-induced epilepsy mouse ( Feng et al, 2021 ). A considerable rise in MDA has been associated with oxidative degradation in cellular proteins ( Miao et al, 2021 ), which we also found.…”
Section: Discussionmentioning
confidence: 98%